CONGENITAL NASOLACRIMAL DUCT OBSTRUCTION: EPIDEMIOLOGY AND RISK FACTORS - Krasina Valcheva; Snejana Murgova; Boris Duhlenski; Irena Hristova (Peytchinski Publishing, 2019)
Purpose: To discuss the various epidemiological aspects and the impact risk factors for developing CNLDO in children. Material/Methods: An analytical observational case-control study. Оne hundred and thirteen children diagnosed and probed for CNLDO in Eye clinic-Pleven were included in a case group. A control group consisted of 121 children without CNLDO. All of the parents answered questions from specially designed questionnaires related to the pregnancy of the mother, antenatal risk factors and child's health in the neonatal period. Results: The demographic profile of the evaluated children in the case group was: 49.6% males and 50.4% females; 33% cases were with affected right eye, 37% left eye, and 30% individuals with bilateral CNLDO after birth. Median gestational age of the children with CNLDO was 40.0. Risk factors for CNLDO development are antibiotics intake and consuming alcohol during the pregnancy. Conclusion: Congenital nasolacrimal duct obstruction affects full-term born children. Detection of the risk factors for developing CNLDO will improve methods for the prevention of this disease.